A study on the characteristic of an eco-brick as a replacement to the conventional brick - Ali, Roslinda; Marsi, Noraini; Mustafa Kamal, Nur Fatin Izzaty; Muhamad, Mimi Suliza; Mohamed Sunar, Norshuhaila; Harun, Hasnida; Abdul Hamid, Hazren; Hamidon, Nuramidah (UTHM Publisher, 2020)
Plastic pollution is a global environmental concern. The increasing urbanization along with population growth rate contributes to an unaccountable amount of plastic waste. Eco-bricks have been identified as one of the measures to reduce the amount of plastic waste disposal at landfills. Eco-brick is a plastic bottle packed with solid non-biodegradable plastic waste. The aim of this study is to investigate the optimum strength of an eco-brick with different density ratios to replace a conventional brick. Five samples of eco-brick with different density ratios were prepared and tested using SolidWorks software version 2014. The tests include compressive test, drop test and failure analysis. From the test results, it can be concluded that density of an eco-brick plays an important role in determining its strength. In addition, the higher the density and the height of the bottle is dropped, the higher is the value of the impact force. The buckling and fracture of eco-bricks with high density ratio are less visible compared to eco-brick with low density ratio.